Sustainability Assessment of the Cultural and Economic Symbiotic System of Yunnan Torch Festival - Shuang Yin; Khalid, Kartini Aboo Talib; Hamzah, Shazlin Amir (Global Sustainability Research, 2026)
The Yunnan Torch Festival is an important traditional festival for the Yi and other ethnic minorities, representing both cultural heritage and cultural tourism resources. However, commercialization driven by tourism development threatens cultural authenticity, necessitating an assessment of the balance between culture and economy. This study constructs a dynamic evaluation system to quantitatively analyze the threshold for balancing cultural preservation and tourism development. A "spatiotemporal zoning" management strategy is proposed, and the effectiveness of digital promotion in attracting youth participation is verified. Based on these findings, a dynamic evaluation matrix is ​​constructed, integrating three dimensions: culture (65%), economy (23%), and technology (12%). An operational threshold rule is introduced: "Preservation Priority" (triggered when cultural authenticity falls below 0.4) and "Commercialization Review" (activated when economic score exceeds 0.7). This provides a scientific decision-making tool for the sustainable development of the Torch Festival's cultural and economic symbiosis and offers a framework for other intangible cultural heritage festivals.